Design and construction of offshore structures proceedings of the conference held on 27-28 October 1976 - Blanc, Jeremy P.; Monro, Mary (Telford for the Institution of Civil Engineers, 1977)
These papers discuss the design of the deck structure for the Sea Platform Constructors (Scotland) Ltd gravity production platform, geophysical and mechanical platform instrumentation, representative sampling for sea bed foundation design and highlight the aims and methods of risk analysis for offshore structures.